Analisis Komparatif Produksi dan Pendapatan Usahatani Padi Studi Kasus Sawah Irigasi dan Sawah Tadah Hujan di Desa Minasa Baji dan Desa Tuppabiring Kabupaten Maros - Jihan Zhafira; Arifin Arifin; Azisah Azisah (Jurnal Agribis, 2023)
Production and Productivity are the main indicators in farming that affect the income of paddy rice farmers. The availability of irrigation water or rainwater for irrigation in paddy rice farming will affect the use of production inputs. The purpose of this study is to determine the amount of production and income of irrigated rice farming and rainfed rice fields in Maros Regency using quantitative descriptive methods. The results of this study show that the production and income of irrigated rice farming is greater than that of rainfed rice fields with a difference in the amount of production of 17,800 kg with a difference in income of Rp. 80,100,000.00.